Streptomyces as a Prominent Resource of Future Anti-MRSA Drugs - Kemung, Hefa Mangzira; Tan, Loh Teng-Hern; Khan, Tahir Mehmood; Chan, Kok-Gan; Pusparajah, Priyia; Goh, Bey-Hing; Lee, Learn-Han (Frontiers in Microbiology, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) pose a significant health threat as they tend to cause severe infections in vulnerable populations and are difficult to treat due to a limited range of effective antibiotics and also their ability to form biofilm. These organisms were once limited to hospital acquired infections but are now widely present in the community and even in animals. Furthermore, these organisms are constantly evolving to develop resistance to more antibiotics. This results in a need for new clinically useful antibiotics and one potential source are the Streptomyces which have already been the source of several anti-MRSA drugs including Vancomycin. There remain large numbers of Streptomyces potentially undiscovered in underexplored regions such as mangrove, deserts, marine and freshwater environments as well as endophytes. Organisms from these regions also face significant challenges to survival which often result in novel bioactive compounds several of which have already shown promise in drug development. We review the various mechanisms of antibiotic resistance in MRSA and all the known compounds isolated from Streptomyces with anti-MRSA activity with a focus on those from underexplored regions. As isolating the full array of compounds Streptomyces are potentially capable of producing in the laboratory has proven to be a challenge and we also review techniques that have been used to overcome this including genetic cluster analysis. Additionally, we review the in vivo work done thus far with promising compounds of Streptomyces origin as well as the animal models that could be used for this work.